2011
DOI: 10.1021/es103552d
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Causes of Sediment-Associated Toxicity in Urban Waterways of the Pearl River Delta, China

Abstract: Twenty-one sediments collected in urban waterways of the Pearl River Delta (PRD) in China were screened for acute toxicity using Chironomus dilutus in addition to being examined for potential contributors of sediment toxicity, including 19 organochlorine, five organophosphate, and nine pyrethroid insecticides, 28 polycyclic aromatic hydrocarbons, 27 polychlorinated biphenyls, 15 polybrominated diphenyl ethers, 12 metals, and ammonia. Fifteen of the 21 sediments exhibited acute toxicity to C. dilutus, with 33% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
83
2
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 28 publications
14
83
2
1
Order By: Relevance
“…It suggested that the riverine input of Zhigao River is an important source of OPs, and it was consistent to a previous finding which reported elevated concentrations of dichlorodiphenyltrichloroethane and its metabolites in water adjacent to Zhigao River and claimed Zhigao River played a key role in insecticides' transport to Chaohu Lake . Generally higher OP concentrations were detected in sediment near the lake shore, and the lowest Holmes et al, 2008;Trimble et al, 2009), Illinois (Ding et al, 2010), and Texas (Hintzen et al, 2009) in USA, the Pearl River Delta Mehler et al, 2011), and Chaohu Lake (the current study) in China.…”
Section: Spatial Distribution and Input Sources Of Sediment-associatementioning
confidence: 46%
“…It suggested that the riverine input of Zhigao River is an important source of OPs, and it was consistent to a previous finding which reported elevated concentrations of dichlorodiphenyltrichloroethane and its metabolites in water adjacent to Zhigao River and claimed Zhigao River played a key role in insecticides' transport to Chaohu Lake . Generally higher OP concentrations were detected in sediment near the lake shore, and the lowest Holmes et al, 2008;Trimble et al, 2009), Illinois (Ding et al, 2010), and Texas (Hintzen et al, 2009) in USA, the Pearl River Delta Mehler et al, 2011), and Chaohu Lake (the current study) in China.…”
Section: Spatial Distribution and Input Sources Of Sediment-associatementioning
confidence: 46%
“…Current-use pesticides (CUPs), such as organophosphates and pyrethroids, have recently been detected in various environmental compartments worldwide (Gan et al, 2005;Hintzen et al, 2009;Li et al, 2013aLi et al, , 2014Mehler et al, 2011;Weston et al, 2005, however, little information is available on their transport within ecosystems. While transport of chlorpyrifos, an organophosphate, has been reported in an airewater system (Harman-Fetcho et al, 2000;Luo and Zhang, 2009;Zhong et al, 2012), studies detailing the transport of pyrethroids have been limited to surface runoff (Gan et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, detection frequency and concentrations of pyrethroid residues have become elevated in the environment [1][2][3][4]. Because of their hydrophobicity, pyrethroids tend to bind to sediment after entering aquatic systems and may contribute more to sediment-associated toxicity than legacy insecticides [5][6][7][8][9][10][11]. A recent study reported that pyrethroids were responsible for approximately 70% of the observed toxicity of sediments collected in urban waterways in the Pearl River Delta (PRD), China [11].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their hydrophobicity, pyrethroids tend to bind to sediment after entering aquatic systems and may contribute more to sediment-associated toxicity than legacy insecticides [5][6][7][8][9][10][11]. A recent study reported that pyrethroids were responsible for approximately 70% of the observed toxicity of sediments collected in urban waterways in the Pearl River Delta (PRD), China [11]. Of the various pyrethroids that were analyzed, cypermethrin was the most commonly detected and attributed the most risk to benthic organisms in the PRD sediments [4,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation